A review of studies on adult second language acquisition within the framework of generative linguistics - Chong, Sharon Yee Ling; Mohd Kasim, Zalina; Jalaluddin, Ilyana; Wong, Ling Yann (Universiti Putra Malaysia Press, 2024)
Despite broad acceptance of the importance of English language in academic and professional contexts in Malaysia, a continuing difficulty persists even at the university level. Malaysians' proficiency levels remain below the intended benchmark, and a variety of reasons, ranging from motivation to familial effects, contribute to this problem. While external factors have been recognized, the learning process remains slow and difficult. This necessitates a research of intrinsic factors, notably those related to the language faculty, in order to understand the underlying reasons that have influenced second language learning. Surprisingly, research on intrinsic variables influencing second language learning difficulty are few in Malaysia, particularly among adults. This literature review seeks to address this gap by providing insights into potential studies focusing on internal factors and emphasizing adults as a critical demographic in understanding and addressing these challenges.